Perception of cultured “meat” by Italian, Portuguese and Spanish consumers - Liu, Jingjing; Almeida, João M.; Rampado, Nicola; Panea, Begoña; Hocquette, Élise; Chriki, Sghaier; Ellies-Oury, Marie-Pierre; Hocquette, Jean-Francois (Frontiers in Nutrition, 2023)
The aim of this study was to investigate how consumers (n = 2,171) originated from South-Western Europe (Italy, Portugal, and Spain) perceive cultured “meat” (CM) and if their demographic characteristics (origin, gender, age, education, occupation, and meat consumption) are related to their willingness to try (WTT), to regularly eat (WTE) and to pay (WTP) for CM. We found the current respondents had an initially positive attitude towards CM: 49% of them perceived CM as “promising and/or acceptable” and 23% “fun and/or intriguing” whereas 29% considered it as “absurd and/or disgusting”. In addition, 66 and 25% would be willing and not willing to try CM, respectively. However, 43% had no WTE for CM and, 94% would not pay more for CM compared to conventional meat. Age and especially occupation were good indicators of consumer acceptance of CM. Respondents of 18–30 years of age had the highest acceptance. Respondents outside the meat sector had the highest WTE and people working within the meat sector had the lowest WTE, scientists (within or outside the meat sector) had the highest WTT, people not scientists but within the meat sector had the lowest WTT. Additionally, we found that men are more likely to accept CM than women, Spanish-speaking consumers had the highest WTT and WTE, people with vegan and vegetarian diets may pay more for CM but generally no more than for conventional meat. The perceptions that CM may be more eco-friendly, ethical, safe and healthy than conventional meat, and to a lower extent, the perception that current meat production causes ethical and environmental problems are likely to be major motives for the current respondents to try, regularly eat and pay for CM. On the opposite, lower perceptions of CM benefits and of conventional meat weaknesses more generally, plus emotional resistance towards CM are main barriers to accept CM.